Culture and the Paradigm of Mainstream Economics - Noga, Marian (Kultura a paradygmat jako główny nurt w ekonomii, 2010)
Arguments are provided in support of the thesis that economics should formulate predictive conclusions, as one of the criteria for theory choice (according to T.S. Kuhn). To satisfy this requirement, the paradigm of mainstream economics should be supplemented with methodological holism, which: accounts for historical and cultural setting of economic behaviours, both on individual and social group level, is complementary (as opposed to substitutive) to methodological individualism, does not disrupt the principles of political and economic freedom, the right of free choice nor the principles of democracy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 106-115
Keywords: culture; paradigm; mainstream economics; methodological individualism; methodological holism